1999
DOI: 10.1038/sj.onc.1203187
|View full text |Cite
|
Sign up to set email alerts
|

SIAH-1 inhibits cell growth by altering the mitotic process

Abstract: SIAH-1, the human homologue of the drosophila seven in absentia gene, is a p53-p21 Waf-1 inducible gene. We report that stable transfection with SIAH-1 of the epithelial breast cancer cell line MCF-7 blocks its growth process. The transfectants show a redistribution of SIAH-1 protein within the nucleus, more speci®cally to the nuclear matrix, associated to dramatic changes in cell morphology and defective mitosis. Multinucleated giant cells (2 ± 12 nuclei in more than 50% cells) were a most striking observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 41 publications
(29 reference statements)
4
41
1
Order By: Relevance
“…These alterations included anomalies of the mitotic spindle and abnormal chromosomal segregation associated with failure of cytokinesis, leading to multinucleated giant cells (Bruzzoni-Giovanelli et al, 1999). In these cells, intercellular bridges containing DNA from non-segregated chromosomes were very common, we observed multipolar spindles evidenced by a-tubulin staining and vacuoles appear in the cytoplasm of multinucleated cells (Bruzzoni-Giovanelli et al, 1999) (Figure 5,1,2). Some mitotic alterations were comparable with those described after Polo kinase gene disruption (Glover et al, 1999) or p21 Waf-1 overexpression (Sheikh et al, 1995).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These alterations included anomalies of the mitotic spindle and abnormal chromosomal segregation associated with failure of cytokinesis, leading to multinucleated giant cells (Bruzzoni-Giovanelli et al, 1999). In these cells, intercellular bridges containing DNA from non-segregated chromosomes were very common, we observed multipolar spindles evidenced by a-tubulin staining and vacuoles appear in the cytoplasm of multinucleated cells (Bruzzoni-Giovanelli et al, 1999) (Figure 5,1,2). Some mitotic alterations were comparable with those described after Polo kinase gene disruption (Glover et al, 1999) or p21 Waf-1 overexpression (Sheikh et al, 1995).…”
Section: Discussionmentioning
confidence: 84%
“…We recently reported that stable transfection of MCF-7 cells by SIAH-1 induced a speci®c phenotype including multinucleated giant cells and altered spindle formation and cytokinesis (Bruzzoni-Giovanelli et al, 1999). In order to identify the possible molecular mechanisms involved in this phenotype, we searched for SIAH-1 interacting proteins using the yeast two-hybrid system.…”
Section: Identification Of Kid and A-tubulin As Siah Interacting Protmentioning
confidence: 99%
See 1 more Smart Citation
“…Other functions of siah-1 involve regulation of cell cycle and pro-survival proteins through protein degradation (22,24,49,52). Whether inhibition of high glucose-induced cell death of Müller cells by siah-1 knockdown results from the inhibition of these alternative functions of siah-1 is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The role of siah-1 in both of these processes, acetylation and phosphorylation of p53, has not been determined and might just be related to transport of GAPDH to the nucleus. On the other hand, a previous study not focused on the interaction between GAPDH and siah-1 has demonstrated a role for siah-1 itself in the process of p53 activation (22). siah-1 and p53 seem to be connected and regulated via a positive feedback mechanism because siah-1 is also regulated by p53 (58).…”
Section: Discussionmentioning
confidence: 99%